miRNAs and lncRNAs as Predictive Biomarkers of Response to FOLFOX Therapy in Colorectal Cancer - Hon, Kha Wai; Abu, Nadiah; Ab Mutalib, Nurul-Syakima; Jamal, Rahman (Frontiers in Pharmacology, 2018)
Chemotherapy is one of the options for cancer treatment. FOLFOX is one of the widely used chemotherapeutic regimens used to treat primarily colorectal cancer and other cancers as well. However, the emergence of chemo-resistance clones during cancer treatment has become a critical challenge in the clinical setting. It is crucial to identify the potential biomarkers and therapeutics targets which could lead to an improvement in the success rate of the proposed therapies. Since non-coding RNAs have been known to be important players in the cellular system, the interest in their functional roles has intensified. Non-coding RNAs (ncRNAs) as regulators at the post-transcriptional level could be very promising to provide insights in overcoming chemo-resistance to FOLFOX. Hence, this mini review attempts to summarize the potential of ncRNAs correlating with chemo-sensitivity/resistance to FOLFOX.